Metapneumovirus Infections and Respiratory Complications - Esposito, Susanna; Mastrolia, Maria Vincenza (Seminars in Respiratory and Critical Care Medicine, 2016)
Acute respiratory tract infections (ARTIs) are the most common illnesses experienced by people of all ages worldwide. In 2001, a new respiratory pathogen called human metapneumovirus (hMPV) was identified in respiratory secretions. hMPV is an RNA virus of the Paramyxoviridae family, and it has been isolated on every continent and from individuals of all ages. hMPV causes 7 to 19% of all cases of ARTIs in both hospitalized and outpatient children, and the rate of detection in adults is approximately 3%. Symptoms of hMPV infection range from a mild cold to a severe disease requiring a ventilator and cardiovascular support. The main risk factors for severe disease upon hMPV infection are the presence of a high viral load, coinfection with other agents (especially human respiratory syncytial virus), being between 0 and 5 months old or older than 65 years, and immunodeficiency. Currently, available treatments for hMPV infections are only supportive, and antiviral drugs are employed in cases of severe disease as a last resort. Ribavirin and immunoglobulins have been used in some patients, but the real efficacy of these treatments is unclear. At present, the direction of research on therapy for hMPV infection is toward the development of new approaches, and a variety of vaccination strategies are being explored and tested in animal models. However, further studies are required to define the best treatment and prevention strategies.
Keywords: acute respiratory tract infections; human metapneumovirus; human metapneumovirus infection; human metapneumovirus vaccine